Primary ovarian leiomyoma associated with multiple uterine leiomyomas - Yoshihiro Kitamura; Fumitake Ito; Tetsuya Kokabu; Taisuke Mori; Izumi Kusuki; Jo Kitawaki (Wolters Kluwer Medknow Publications, 2021)
Ovarian leiomyomas are very rare. We report the case of a primary ovarian leiomyoma accompanied by multiple uterine leiomyomas. A 50-year-old woman was referred to our department for heavy menstruation, and a hot spot in the uterine lumen was observed on positron emission tomography-computed tomography (PET-CT). Cervical and endometrial cytology and tumor marker tests were negative. Pelvic magnetic resonance imaging revealed an endometrial polyp and submucosal leiomyoma in the uterine lumen and a 5-cm right ovarian tumor. Laparoscopic total hysterectomy, right salpingo-oophorectomy, and left salpingectomy were performed for radical treatment. Histopathology showed that ovarian tumors contained interlacing bundles of fusiform cells encircled by normal ovarian tissue. Immunohistochemical staining showed strong and diffuse positive staining for α-smooth muscle actin. We diagnosed the tumor as a primary ovarian leiomyoma because the leiomyoma was localized in the ovary and was larger than the size of uterine leiomyomas. No metastatic lesion was found on PET-CT. There was no tumor recurrence at the 6-month follow-up.